"Spiegeldorf" Nazi Appeals in Weimar Germany - Sprague, Gregory A. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
The paper discusses rationales for simulation gaming and describes "Spiegeldorf," a socio-historical game which simulates socioeconomic conditions in early 1930 Germany and Nazi party tactics used to gain mass support. Objectives are to identify characteristic Nazi tactics and points of political ideology, describe German social classes and their fears and frustrations, analyze ways Nazism appealed to many Germans, and increase student interest in the subject and enjoyment in playing the game. Each student plays the role of a Nazi party organizer, whose goal is to convert as many people as possible. Play proceeds through choosing one of five tactics and receiving outcome cards and conversion points. With the appointment of Hitler as Chancellor of Germany, each student adds up the number of converts and ascertains the final outcome. Time allotment is 90 minutes. Materials include a game board, information sheets, conversion checklists, outcome, event, and influence cards, and a debriefing guide. Discussion analyzes the cause-and-effect relationships affecting the payoff through exploration of student feelings, explanation of strategies, and examination of concepts and principles. Evaluation criteria were historical accuracy, positive student attitudes, and an increase in student knowledge. Use of subject authorities ensured accuracy, while attitudes and knowledge were measured through observation, a questionnaire, and a posttest. Sample game materials and questionnaire results are appended. (CK)
ERIC Note: A paper presented at the Annual Meeting of the American Historical Association (San Francisco, California, December 28, 1978).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Class Activities; Educational Games; Educational Objectives; European History; Evaluation; Higher Education; History Instruction; Instructional Materials; Interaction Process Analysis; Models; Political Influences; Propaganda; Relationship; Role Playing; Simulation; Social Class; Social History; Social Structure; Speeches; Teaching Methods; Totalitarianism; Nazism; Germany; Guides, Classroom -- Learner; Guides, Classroom -- Teacher; Speeches/Meeting Papers